Marriott and the Amazon Foundation: an example of strategic sustainability - Fogel, Daniel S. (Henry Stewart Talks, 2019)
This case study examines Marriott’s support for Fundação Amazonas Sustentável (the Sustainable Amazon Foundation), an organisation dedicated preserving the Amazon rainforest. Deforestation would harm Marriott’s profitability in the region and thus by supporting Fundação Amazonas Sustentável’s sustainability agenda, Marriot is supporting its own business.
Archived at 2024/02/11